PEMBERDAYAAN PETUGAS KESEHATAN GIGI PANTI SOSIAL DALAM MELAKUKAN PEMELIHARAAN KESEHATAN GIGI DAN MULUT - Isnawati; Sri Nuryati; bunga nurwati (UPPM Poltekkes Kemenkes Banjarmasin, 2026)
Based on the results of a survey conducted at the Fajar Harapan Martapura Social Home for the Blind, South Kalimantan, of 10 blind people, 7 of them still don't know how to brush their teeth properly and correctly. This is what prompted the author to carry out activities to empower dental health workers at social institutions in carrying out dental and oral health maintenance with the aim of increasing dental and oral health knowledge and teeth brushing skills for blind people at the Fajar Harapan Martapura Social Institution for the Blind, South Kalimantan. The implementation methods used include conducting a needs survey by conducting interviews with several assistants for the blind at the Fajar Harapan Martapura Social Care Home for the Blind, South Kalimantan Province, and preparing tools and materials. Next is the implementation of activities, starting from preparation to monitoring, evaluation of output achievements and achievement of output targets within a period of 6 months (April to September). The result of this activity was that the oral prophylaxis assistance activity was successful (100%) and all participants were very cooperative. During tartar cleaning activities (scaling) was only 6.4% successful because only 10 out of 64 people were willing to have tartar cleaned. All participants who were cleaned had poor OHIS criteria, while simple ART filling activities could not be carried out because the dental caries cases were very deep and could not be carried out. direct or direct extermination.